Pengaruh Disiplin Kerja, Psychological Capital dan Perceived Organizational Support Terhadap Kinerja Pegawai Negeri Pada Bareskrim Polri (Studi Terhadap Penyidik Polri) - Herawati Supristyaning Hartanti (Pusat Penelitian dan Pengembangan Polri, 2022)
Investigation Police are members of the National Police given a special task of conducting investigations. The performance of investigators directly visible to the public it can affect the level of public trust in the Institution of National Police. The performance of investigators have to improved as an effort to increase public trust in Institution of National Police and to deal with criminal problems professionally and proportionally This study aims to determine the effect of Work Discipline, Psychological Capital and Perceived Organizational Support on the Performance of Criminal Investigation Police. The independent variables in this study are Work Discipline, Psychological Capital and Perceived Organizational Support. While the dependent variable in this study is the Government Employees at Bareskrim(case for Polri Criminal Investigator Performance). The sampling method in this study uses probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a sample member with a total of 392 people with 198 filling out complete questionnaire data. The research analysis method used is the Structural Equation Model (SEM) based on The Partial Least Square (PLS). From the results of the analysis of research that has been done shows that: 1) Work Discipline Variable has a positive effect on the variable Performance of Investigators in Criminal Investigation Police; 2) Psychological Capital has a positive effect on the level of performance of Investigators in the Criminal Investigation Police Unit; 3) The positive influence of Perceived Organizational Support on the Performance of Criminal Investigation Police Officers; and 4) Work discipline, Physcological Capital and Perceived Organizational Support are proven to have a positive and significant effect on performance. Keywords: Work Discipline, Psychological Capital, Perceived Organizational, Performance